Effect of Al2O3 and B4C particle additions on microstructure of PM copper based brake linings - Uzunsoy, D. (MANEY PUBLISHING, 2008)
This paper highlights the effect of different ceramic particles on the structure of PM copper based brake linings. The copper based brake linings using a range of ceramic additives (1-6 wt-%) were prepared by powder metallurgy (PM). The optimum conditions for the production of brake linings were determined as compaction under 400 MPa and sintering at 805 degrees C for 20 min in an argon atmosphere. The density of copper based brake linings decreased after sintering with the increase in ceramic powder contents for both Al2O3 and B4C ceramic particles. The microstructural characterisation of produced samples showed that the lower boiling point elements in the as supplied powder vaporise during sintering from the structure and this leads to an increase in the porosity amount of the final component.
Keywords: Friction materials; Powder metallurgy; Brake linings; Ceramic particles; Microstructure; PERFORMANCE; Metallurgy & Metallurgical Engineering